CONGENITAL ANOMALIES OF THE GASTROINTESTINAL TRACT AMONG THE NEWBORN IN BAKU CITY - Seyidbekova, F.O. (World of Medicine and Biology, 2013)
The analyses of frequency of the occurrence of congenital anomalies was conducted in Baku in period for 2000-2011 years. For this period of time the 1070 newborn are educed with different congenital anomalies/ from them in 150 cases was diagnosed congenital anomalies of gastrointestinal tract. The height of such pathologies, as pyloristenosis, was marked that 0,8 cases on 10000 new born in 2005 year to 2,8 cases in 2011 year of the anus from 1,4 to 2,4 cases. These indexes once again talks about actuality of this theme.
Keywords: frequency of the occurrence; congenital anomalies of gastrointentestinal tract; newborn